Civil rights regulations - Salm, Erich
Regulations pertaining to civil rights of foreign nationals living in Spain.
Facsimile.
Collection material in German, with marginal notes in Spanish.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Aliens -- Civil rights -- Spain; Germans -- Spain -- History -- 19th century